Commercializing academic knowledge and reputation in the late nineteenth and early twentieth centuries: photography and beyond. (2nd January 2017) - Mercelis, Joris
Abstract: This article argues that Hermann Vogel (1834–1898), the head of the photochemical laboratory of the Technische Hochschule Berlin-Charlottenburg, was not exceptional in pursuing business undertakings throughout his academic career. After highlighting the involvement of higher education employees of various disciplines and institutions in the photographic industry as consultants, patentees, and entrepreneurs, I more closely examine the commercial activities of Vogel and those of Adolf Miethe (1862–1927), Vogel's successor in Berlin. This analysis points to a notable continuity through time. It shows that these scientists' decades-long engagement in commercial work was not materially affected by (1) their salary levels, (2) the emergence of industrial research in the photographic and optical industries, and (3) changes in the amount of government funding for scientific research. In addition, it reveals that the Prussian education ministry maintained a strong focus on reputational risks in handling complaints concerning commercial activities of these academics.